The effect of lipid on the digestion of cellulose by the ruminant : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Animal Science at Massey University - Kirk, Robin David (Massey University, 1969)
1.Metabolism of Lipids by Ruminants Many workers have added fats, oils and fatty acids to the rations of sheep, beef cattle and dairy cows to investigate the effects of lipid on either one or more of the following; intake, digestibility end energy utilisation of rations, live weight gains, methane production, ammonia production, N retention, milk production, milk constituents, total VPA production and VFA molar proportions or the value of lipid as a source of energy. These factors will be discussed in subsequent sections of this review. Lipids which have been fed or infused into ruminants include coconut, cod liver, corn, cottonseed, linseed, palm kernel, peanut, soyabean, tung and whale oils, animal fats (lard, tallow and poultry fat) and long chain fatty acids (palmitic, stearic, oleic, linoleic and linolenic). Since the amount of lipid ingested by adult ruminants is substantial, the investigations into the effects of lipids are warranted. A cow consuming 45Kg. of pasture daily will ingest about 500g. of lipids and, under conditions of stall-feeding, pregnant and lactating animals may receive rations which provide up to 1.0Kg. of lipids daily (Garton, 1967).[FROM INTRODUCTION]
Keywords: Ruminants; Digestive organs; Physiology; Lipids; Cellulose; Metabolism